Antioxidant and Antimicrobial Properties of Helichrysum italicum (Roth) G. Don Hydrosol - Katja Bezek; Katja Kramberger; Darja Barlič-Maganja (MDPI AG, 2022)
(1) Background: According to the emergence and spread of antibiotic resistance, there is an urge for new promising substances. The purpose of the study was to test the antioxidant, cytotoxic and antimicrobial properties of the Helichrysum italicum (Roth) G. Don essential oil (EO) and hydrosol. (2) Methods: The antioxidant potential was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The cytotoxicity for human skin and intestinal cells was tested using primary and immortalized cell line models. The minimum inhibitory concentration (MIC) of hydrosol was then determined for six bacterial strains covering four commonly reported food pathogens. Further on, the hydrosol at a concentration of 1/8 MIC was used to test the antiadhesive effect by the crystal violet (CV) staining method. (3) Results: the EO showed a 100-times higher antioxidant and 180- to 25.000-times higher cytotoxic activity, when compared to hydrosol. Nevertheless, all bacterial strains, with the exception of Staphylococcus aureus, were sensitive to hydrosol in the range of 12.5% (V/V) for Campylobacter jejuni, to MIC values of 100% (V/V) for Escherichia coli and Pseudomonas aeruginosa. The antiadhesive potential of hydrosol was also shown. (4) Conclusions: Even though hydrosols are a by-product of the EO distillation process, they possess valuable biological activities.